Generating Consumer Loyalty: The Role of System Quality, Social Influence and Mediation of Perceived Ease of Use and Perceived Usefulness - Darma Shiva, I Komang Wahyu; Fredy Maradona, Agus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Shopee is the leading online shopping platform in Indonesia that provides a safe, fast and easy online shopping experience, with a reliable payment and logistics system. Shopee aims to be the leading e-commerce choice in Indonesia and offers various product categories, including Electronics, Home Appliances, Health, Beauty, Mother & Baby, Fashion, and Sports Equipment. Launched in 2015 as part of the Sea Group, Shopee is present in various countries, including Singapore, Malaysia, Thailand, Taiwan, Indonesia, Vietnam and the Philippines. The reason researchers use Shopee as a research object is because Shopee is one of the most popular e-commerce sites in Indonesia at the moment. The existing phenomenon is that there are indications that Shopee consumer loyalty is not maintained and the quality of the system owned by Shopee is not optimal. This type of research is descriptive quantitative research. In this research, the research location chosen was in Indonesia. Because the research subjects were those who had shopped at Shopee. Indonesia has more than 100 million active e-commerce users. The sampling method used was the accidental sampling method, the sample for this research was 156 people. The data collection technique used in this research is using a questionnaire technique. In this research, a questionnaire is used to measure certain variables using a Likert scale. The descriptive analysis used in this research is PLS software. In this research, hypothesis testing uses the Partial Least Square (PLS) method. The results of this research show that system quality has a negative effect on customer loyalty, meaning that a higher system quality level does not mean it will increase customer loyalty. Social influence has a positive effect on customer loyalty, meaning that the higher the level of social influence, the higher the possibility of customer loyalty. Perceived ease of use has a positive effect on customer loyalty, meaning that the better the perceived ease of use, the higher the possibility of customer loyalty.